The Multiple Aspects of Stroke and Stem Cell Therapy - Onteniente, B. (Current Molecular Medicine, 2013)
Cumulative evidence shows that transplantation of stem cells (SC) derivatives can reduce the functional deficits induced by cerebral ischemia or hemorrhage in animals. Most SC sources have been applied to stroke models, with varying degrees of differentiation into neural derivatives and in varying number, timing and route of administration, with similar benefits on functional outcome. Pioneering clinical trials developed in parallel, and currently outnumber other applications of SC in neurological disorders. These trials reflect a paradigm shift from cell replacement therapy to disease-modeling effects, with increased used of nonneural SC. This shift stems in experimental demonstration of paracrine effects of SC that attenuate inflammation, limit cell death through neurotrophic effects, and enhance endogenous recovery processes. Due to its pathogenic characteristics, stroke can uniquely benefit from this variety of actions.
Keywords: intracerebral transplantation